Islam dan budaya: Indonesia - Khasanah, Sintia Nurul (Maliki Interdisciplinary Journal, 2024)
Indonesia is a country rich in various cultures and traditions. This influences and impacts the religious values that develop in society, especially the values that come from Islam and their native culture. Therefore, this paper will discuss the values of Islam and Indonesian culture and how these two values can coexist and harmonize in everyday life. Sometimes in Indonesian society, Islamic values and Indonesian cultural values are considered as two different and conflicting things. However, Islamic values and Indonesian culture have a very close relationship and strengthen each other. In addition, this paper will explain the importance of harmonization between Islamic values and Indonesian culture in the life of Indonesian society. It is hoped that with this paper, readers will better understand the values contained in Islam and Indonesian culture and the importance of applying these values in everyday life.